The Problem of Political-Geographical Self-Identification of the Baltic States: the Historical Past vs the Objective Present - V. Vorotnikov; A. Chekov (Международная аналитика)
Today, the term "the Baltic states" is used, as a rule, as an umbrella-name for the three former Soviet republics - Estonia, Latvia and Lithuania. The grounds to unify them into a single construct are, above all, their geographical location, as well as some parallels of state development, deeply rooted in the mass consciousness. However, the problem of whether these grounds are sufficient to speak of a single "Baltic identity" shared by three states, or whether its unifying potential is limited to providing an "umbrella term" convenient under certain circumstances, is still a matter of research interest. How relevant today is the idea of a unified "Baltic identity" of Estonia, Latvia and Lithuania, and how does it correlate to other types of political and geographical identities of these countries?